Genetic diversity of mastitis cow’s milk bacteria based on RAPD-PCR (Biodiversitas Journal of Biological Diversity, 2018)
Mustopa AZ, Puspitasari IF, Fatimah, Triratna L, Kartina G. 2018. Genetic diversity of mastitis cow’s milk bacteria based on RAPD-PCR. Biodiversitas 19: 1714-1721. Mastitis in cow is caused by several pathogenic bacteria, including antibiotic-resistant bacteria. Identification of the pathogenic bacteria’s diversity that is contaminating cow’s milk needs to be done. The aim of this research was to conduct molecular identification in mastitis cow’s milk bacteria through RAPD-PCR (Random Amplified Polymorphism DNA-Polymerase Chain Reaction) analysis. Bacteria from mastitis cow’s milk were enumerated using selective media. Based on the result of media selection, there were 72 isolates of bacteria from mastitis cows in Ciguha, Guranteng, Cikarenceng Village (Pagerageung, Tasikmalaya), and Warnasari Village (Pangalengan, Bandung), West Java, Indonesia. The genomes from these isolates were extracted and then subjected to RAPD-PCR analysis. The results of RAPD-PCR analysis showed 8 clusters of dendrogram which 4 dominant clusters were selected. Identification of 4 dominant clusters, which contained representative strains, using 16s rRNA showed the isolates BPA-12, MHA-6, L-4, and XLDA-8 were identified as Staphylococcus aureus, Escherichia coli, Listeria monocytogenes, and Enterobacter bugandensis.
Keywords: 16S rRNA analysis; mastitis cow’s milk bacteria; RAPD-PCR analysis